Characterization of the alpha-tubulin gene family of Arabidopsis thaliana. - Ludwig, S R (1987)
The genome of Arabidopsis thaliana (Linnaeus) Heynhold was shown to contain an alpha-tubulin gene family consisting of at least four genes and/or pseudogenes. The primary structure of a transcribed alpha-tubulin gene was determined. A comparison of the predicted amino acid sequence of the A. thaliana alpha-tubulin with the predicted amino acid sequences of alpha-tubulins of Chlamydomonas reinhardtii, Stylonychia lemnae, and Homo spaiens reveals a high degree of homology; 90%, 87%, and 83% identity, respectively. Thus, a plant alpha-tubulin exhibits a high degree of homology to the alpha-tubulins of protists and animals. The coding sequence of the A. thaliana alpha-tubulin gene is interrupted by four introns, which occur at positions different from those of the less numerous introns of C. reinhardtii and rat alpha-tubulin genes. S1 nuclease mapping data showed that transcription is initiated 99 +/- 1 base pairs upstream from the translation initiation codon. Both 5' and 3' noncoding gene-specific probes were used to examine the expression of the alpha-tubulin gene in leaves, roots, and flowers by hybridization to total RNA isolated from these tissues. The results showed that the alpha-tubulin gene was transcribed in all three tissues.